On the existence of SER403 active site adjacent cleft of methicillin resitance SAUPBP2A (MRSA) - Van, Dang Ung; Mi, Nguyen Hoa (Vietnam Journal of Chemistry, 2012)
By comparing the crystal structure of apo enzyme PBP2a* and its acyl complexes with methicillin and nitrocefin we exploit an active site adjacent cleft which has closed and open situation. The existence of a two conformation adjacent cleft of the active site should be paid attention in resistance mechanism. The cleft closed conformation detected in SauPBP2a apoenzyme structure prevents β-lactam far from active site. The cleft open conformation observed in SauPBP2a structure of acyl complexes allows β-lactam molecule pass over approaching the position suitable for nucleophilic attack. Using a combination of AutoDock docking and GROMACS molecular dynamics software we confirm the cleft existence, its two situation and the ability of conformation change from closed to open situation which appropriate for acylation process.